The lithospheric S-wave velocity structure beneath the NE Tibetan Plateau and its surrounding craton basins - Wang, Weilai; Cai, Guangyao; Wu, Jianping; Fang, Lihua (Frontiers in Earth Science, 2023)
It is essential to investigate the spatial distribution of the lithosphere and asthenosphere in detail, to further obtain the understanding of the effect of plate collision and the process of orogenic movement. From the joint inversion of receiver functions and surface waves, the three-dimensional S-wave velocity structure results down to 200 km depth in the study area were obtained at 1,843 seismic stations. Analysis was performed on the sedimentary thickness, crustal thickness, lower crustal wave velocity, and lithospheric thickness. According to the crustal thickness, we evaluated the distribution of low-velocity zones in the lower crust. The results show that there are low-velocity bodies in the lower crust in the Qinling tectonic belt, but they are not connected, indicating that they may not be able to be used as a channel for material extrusion from the NE Tibetan Plateau at the crustal scale. According to the section results and the depth distribution of the lithosphere-astenosphere boundary, a relatively thick lithosphere exists below the Sichuan Basin and Ordos Basin, and the lithosphere in the east of the study area is relatively thin with a thickness of about 60-80 km, indicating that the lithosphere in the east of the study area has been severely destructed and restructured. The delamination has been observed in the lithosphere under the Songpan-Ganzi Block, showing characteristics of vertical movement of asthenosphere materials. There is a relatively thick low-velocity zone at the top of the mantle lithosphere of the NE plateau; however, it does not exist under the relatively stable Sichuan Basin and the Ordos Block. Compared with the Sichuan Basin and the Ordos Basin at both sides, the Qinling tectonic belt has a low-velocity zone at the depth of 100-160 km, which may be asthenosphere material. In combination with the polarization direction characteristics of the SKS wave, it is clearly observed that asthenospheric material movement exists in an approximate east-west direction beneath the Qinling tectonic belt. Therefore, the asthenosphere beneath the Qinling tectonic belt may serve as an important channel for material extrusion in the NE Tibetan Plateau.